Electricity - Saving Behavioral Intention of Farmers - Mai, Van Nam; Nguyen, Quoc Nghi (International Journal of Energy Economics and Policy, 2023)
The study applied the Theory of Planned Behavior - TPB (Ajzen, 1991) and the Norm Activation Model - NAM (Schwartz, 1977) to demonstrate the affecting factors on behavioral intention in energy saving of farmers in the Mekong Delta, Vietnam. Research data were collected from 204 farmer households using electricity in four provinces: Tien Giang, Dong Thap, An Giang, and Kien Giang. Applying the structural equation modeling (SEM), the study has pointed out the affecting factors mentioned above, including personal ethical standards, subjective norms, perceived behavioral control, perceived benefit, attitude, product quality, and energy policy. Besides, the study has shown that the intention to save electricity positively impacts the electricity-saving behavior of farmers